1991
DOI: 10.1111/j.1600-0447.1991.tb03144.x
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of early diagnosis and predictors of death in Alzheimer's disease and vascular dementia — a follow‐up study

Abstract: A total of 87 patients with mild or moderate degree of dementia of the Alzheimer type (AD) or vascular dementia (VD) was identified (DSM-III criteria), and their cognitive capacity was evaluated by means of rating scales and psychometric tests. Three years later 30 patients (34%) were dead. Significantly more VD than AD patients died. Eight of the survivors declined to participate in a follow-up study, and 1 patient was excluded by mistake. Of the survivors, 17 had indisputably suffered cognitive decline durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…On the other hand, physicians may tend to underdiagnose comorbid illnesses because demented patients might be unable to explain or recall specific complaints, and/or to collaborate during the diagnostic workup. While comorbidity is believed to be accurately measured even among the oldest-old nursing home residents [11,12], our findings show, indeed, underdiagnosis (and undertreatment) of certain conditions like depressive disorders. Nonetheless, while this hypothesis cannot be conclusively tested, understanding why 'protection' is afforded only against certain diseases remains unclear.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…On the other hand, physicians may tend to underdiagnose comorbid illnesses because demented patients might be unable to explain or recall specific complaints, and/or to collaborate during the diagnostic workup. While comorbidity is believed to be accurately measured even among the oldest-old nursing home residents [11,12], our findings show, indeed, underdiagnosis (and undertreatment) of certain conditions like depressive disorders. Nonetheless, while this hypothesis cannot be conclusively tested, understanding why 'protection' is afforded only against certain diseases remains unclear.…”
Section: Discussionmentioning
confidence: 82%
“…Yet, only a limited number of studies have investigated the prevalence and impact of comorbidity on functional status and mortality in relation to different degrees of cognitive impairment [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most fi ndings in studies based on representative samples as well as on clinical studies have shown either a more favorable course of Alzheimer's disease (AD) [7,19,25,56,57] or no difference between AD and vascular dementia (VD) [29,50,58,59] . Our results support these fi ndings.…”
Section: Factors Associated With Early Death Within the Group Of Incimentioning
confidence: 99%
“…LIMINATING weight loss and malnutrition is a priority because of their association with an increased risk of morbidity (1), mortality (2,3), and greater rates of disease progression in seniors with Alzheimer's disease (AD; 3). Although weight loss in AD is well documented (4)(5)(6)(7)(8)(9)(10) and considered a clinical feature consistent with this diagnosis (11), its etiology remains elusive.…”
mentioning
confidence: 99%